We have to prove (a rem n) = a (mod n).
Now I know a rem n is whatever the remainder is of a/n. And for mod its usually z = a (mod n) = n / (z-a). I'm just not sure how to prove the problem above. Any suggestions because I know this is probably easy, i'm just not getting it.
So after writing out the defined remainder a = y*n + z
Do I try to work it out so it equals y = n/ z-a? which would represent z = a (mod n) and prove (a rem n) = a (mod n)?
You can't work out a = yn + z to equal y = n/ z-a.
Is there something else that i'm missing? is the (a rem n) = a (mod n) = y ?